Masjid Kraton Sambas dalam Konstelasi Pembaharuan Islam di Kalimantan Barat - Murtadlo, Muhamad (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2014)
The mosque is an important witness in the spread of Islam and the shift in religious thought in the community. This article attempts to examine the role of one of the Sultan Mosque in West Kalimantan, the Sultan of Sambas Mosque. This study uses the approach of religious archeology which is supported by tracing the history. The findings of this study found: 1) the existence of Sultan Sambas Mosque are witnessing the present Â of Islam in West Kalimantan and the architecture of this mosque perform of the accumulation of these objects makes Sultan Sambas Mosque is a symbolic fusion of cultures of various countries. Therefore, cosmopolitan culture already visible in the architecture of the palace mosque Sambas. 2) Sultan Sambas Mosque play an important role in the renewal of Islamic thought in West Kalimantan. Keywords: Sultan Mosque, Sambas, Architecture, Islamic Renewal, Imam Mosque